2020
DOI: 10.1097/sla.0000000000003791
|View full text |Cite
|
Sign up to set email alerts
|

Safe Cholecystectomy Multi-society Practice Guideline and State of the Art Consensus Conference on Prevention of Bile Duct Injury During Cholecystectomy

Abstract: Background Bile duct injury (BDI) is the most common serious complication of laparoscopic cholecystectomy. To address this problem, a multi-society consensus conference was held to develop evidenced-based recommendations for safe cholecystectomy and prevention of BDI. Methods Literature reviews were conducted for 18 key questions across six broad topics around cholecystectomy directed by a steering group and subject experts from five surgical societies (SAGES, AHPBA IHPBA, SSAT, and EAES). Evidencebased recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 164 publications
(181 reference statements)
0
94
0
4
Order By: Relevance
“…It would seem unlikely that surgeons not understanding this simple concept or that the lack of photographic documentation of the CVS is to blame for biliary injuries. A multi-society consensus conference on prevention of bile duct injury during cholecystectomy suggested that no direct comparative evidence was identified to support the critical view of safety (CVS) over other methods for anatomic identification [16]. It concluded that there is no substantial evidence that reasonable efforts to achieve the CVS have been associated with undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…It would seem unlikely that surgeons not understanding this simple concept or that the lack of photographic documentation of the CVS is to blame for biliary injuries. A multi-society consensus conference on prevention of bile duct injury during cholecystectomy suggested that no direct comparative evidence was identified to support the critical view of safety (CVS) over other methods for anatomic identification [16]. It concluded that there is no substantial evidence that reasonable efforts to achieve the CVS have been associated with undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…BDI rate has plateaued over the last time and is close to the open cholecystectomy era ranging between 0.15% and 0.36%. 6,7 The most common cause of BDI is misidentification of the visualized anatomical structures. Noteworthy is also surgeon skill and anatomical variations in the hepatocystic triangle.…”
Section: Discussionmentioning
confidence: 99%
“…There are no recommendations if the conversion limits the risk or severity of BDI during difficult laparoscopic cholecystectomy. 7 It does not always provide a better view of the anatomy and may be associated with a higher risk of BDI and VBI. The younger generation of surgeons is not familiar with this technique.…”
Section: Laparoscopic Ultrasound and Shrunken Gallbladdermentioning
confidence: 99%
See 2 more Smart Citations